Kebahagiaan Dosen Ditinjau dari Iklim Keluarga: Peran Mindfulness Sebagai Mediator - Rusmalia Dewi; Rini Sugiarti; Erwin Erlangga; Tatas Transinata; Yudi Kurniawan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The main happiness of Lecturers is when they feel healthy in body and soul, one of which is by getting attention from their closest family. The culture of collectivism in Indonesian people, coupled with the ability of lecturers to do mindfulness in every activity is very helpful in creating personal happiness. The lives of lecturers often experience problems with their workplace and also their families, therefore the importance of a support system from the family so that lecturers are able to carry out their daily activities at work happily. The purpose of this study is to empirically test the happiness of Lecturers as reviewed from the family climate through the role of mindfulness as a mediator variable. The method used is quantitative, using 250 Lecturer respondents in the city of Java. Using purposive sampling techniques and data analysis methods using multiple linear regression with the Hayes program. The results showed that family climate had an influence of R = .539 sig.0.01 on lecturer happiness through mindfulness. Mindfulness is able to be a partial mediator of family climate on lecturer happiness. This study has implications so that it can be used as a reference for the application of Lecturer happiness through the family's internal support system.